(untitled) (Research, Society and Development, 2023)
The purpose of this study was to evaluate the influence of clinical and subclinical pregnancy toxemia (PT) on blood metabolites of dairy goats in the peripartum period. 111 multiparous goats were divided into three groups on the basis of cut-off blood concentrations of β-hydroxybutyric acid and clinical symptoms of PT. The control group (n=40, βHB ≤ 0.8 mmol/L), whereas the subclinical group (n=39, βHB between 0.8 and 1.6 mmol/L) and the clinical group (n=32, βHB ≥ 1.6 mmol/L). The evaluations were performed on the -30, -20, -10, 0, +10, +20, and +30 day in relation to parturition. βHB, non-esterified fatty acid, glucose, fructosamine, cholesterol, triglycerides, insulin, cortisol, and free T3 and free T4 were measured. The ANOVA was performed to investigate the effects and interactions between groups and assessment times using the SAS. A higher occurrence of clinical PT was observed during late pregnancy, whereas subclinical PT was more frequently in early lactation. Clinical and subclinical PT during the transitional period resulted in raising the βHB, NEFA, and cortisol (P<0.05). Meanwhile, a decrease was observed in fructosamine, triglycerides and insulin (P<0.05). The occurrence of subclinical PT was higher than the clinical form during peripartum. The βHB validated the possibility of detecting goats that are at a high risk of developing PT approximately three weeks before parturition. Clinical and subclinical PT triggered marked changes in serum concentrations of βHB, NEFA, insulin, and cortisol, being those biomarkers in potential of PT.